2004
DOI: 10.1021/es0349709
|View full text |Cite
|
Sign up to set email alerts
|

Colloid Formation in Hanford Sediments Reacted with Simulated Tank Waste

Abstract: Solutions of high pH, ionic strength, and aluminum concentration have leaked into the subsurface from underground waste storage tanks atthe Hanford Reservation in Washington State. Here, we test the hypothesis that these waste solutions alter and dissolve the native minerals present in the sediments and that colloidal (diameter < 2 microm) feldspathoids form. We reacted Hanford sediments with simulated solutions representative of Hanford waste tanks. The solutions consisted of 1.4 or 2.8 mol/kg NaOH, 0.125 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 27 publications
3
41
1
Order By: Relevance
“…A 2.8 general mineral transformation pathway was observed in these studies: poorly crystalline aluminosilicate fi Linde Type A zeolite fi cancrinite/sodalite, with cancrinite and sodalite being the two stable phases (Deng et al 2006a). In earlier studies, the same group found that cancrinite, sodalite, LTA zeolite and allophane were identified as the new formation in these sediments (Mashal et al 2004;Mashal et al 2005b;Mon et al 2005). The soil mineral dissolution followed the order of quartz fi kaolinite fi illite, and although cancrinite, sodalite, and zeolite were formed, the zeolite was not detected after 25 days of reaction time (Mashal et al 2005a), indicating that this mineral underwent either dissolution or phase transformation.…”
Section: 7supporting
confidence: 51%
“…A 2.8 general mineral transformation pathway was observed in these studies: poorly crystalline aluminosilicate fi Linde Type A zeolite fi cancrinite/sodalite, with cancrinite and sodalite being the two stable phases (Deng et al 2006a). In earlier studies, the same group found that cancrinite, sodalite, LTA zeolite and allophane were identified as the new formation in these sediments (Mashal et al 2004;Mashal et al 2005b;Mon et al 2005). The soil mineral dissolution followed the order of quartz fi kaolinite fi illite, and although cancrinite, sodalite, and zeolite were formed, the zeolite was not detected after 25 days of reaction time (Mashal et al 2005a), indicating that this mineral underwent either dissolution or phase transformation.…”
Section: 7supporting
confidence: 51%
“…Our review suggests that colloidfacilitated transport has generally been overstated in site assessments described in this study. This position also is supported by Hanford-specific studies demonstrating that colloid facilitated transport of highly sorptive contaminants in groundwater is minimal (Flury et al 2002;Cherrey et al 2003;Zhuang et al 2003Zhuang et al , 2004Marshal et al 2004;Dai et al 2005;Czigany et al 2005). Colloid-facilitated transport of highly sorptive contaminants in the vadose zone would be expected to be even less than in saturated groundwater, due to the much higher ratio of surface area to water volume and thin water-film thicknesses, which would be conducive to filtration of particles from solution.…”
Section: Summary and Implications For Hanfordmentioning
confidence: 85%
“…Important micaceous sorbents (including biotite) may also dissolve in this zone Samson et al 2005). Hydroxide alkalinity is transformed to silica and aluminate alkalinity in this zone (Marshal et al 2004). Below this zone, where depth is controlled by the volume of tank waste release, exists a pH neutralization zone (pH 6.5 -10), where protons are released for additional base neutralization by the secondary precipitation of complex suites of zeolitic phases including cancrinite; feldspathoids, such as sodalite, ettringite, and gibbsite; and other unnamed aluminosilicates (Ainsworth et al 2005;Chorover et al 2003;Deng et al 2006;Qafoku et al 2004;Wan et al 2004a;Wan et al 2004b;see Figure 6.8).…”
Section: 22mentioning
confidence: 99%
“…Hydroxide and other anion concentrations are critical variables determining secondary mineral precipitate phase identity and morphology. The precipitates exist as both grain coatings (Ainsworth et al 2005;Qafoku et al 2004) and suspended colloids in the aqueous phase exhibiting negative surface charge (Marshal et al 2004). …”
Section: 22mentioning
confidence: 99%
See 1 more Smart Citation